2016
DOI: 10.1016/j.biombioe.2016.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of methane yields from anaerobic digestion of dairy cattle manure

Abstract: This work presents a novel meta-analysis for methane yields from anaerobically digesting dairy cattle manure. A database is compiled from 115 articles (2,181 cases) by systematically assessing the academic literature. Y CH4 and secondary variables collected in the database describe performance, operation conditions of digester and manure composition. Inputs to the database are normalised to enable inter-study uni-and multi-variate analysis, according to different types of digesters. Most cases (N=1,299) are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 38 publications
(45 reference statements)
0
9
1
2
Order By: Relevance
“…The production of RNG from the addition of hydrogen to anaerobic digested biogas is an area of increasing importance . There are currently 244 anaerobic digesters operating in farms in the United States of America, with animal manure as the only feedstock .…”
Section: Assessing the Potential Of Renewable Natural Gas Productionmentioning
confidence: 99%
“…The production of RNG from the addition of hydrogen to anaerobic digested biogas is an area of increasing importance . There are currently 244 anaerobic digesters operating in farms in the United States of America, with animal manure as the only feedstock .…”
Section: Assessing the Potential Of Renewable Natural Gas Productionmentioning
confidence: 99%
“…34 As shown in Figure 3, the total biogas production of the U3 experimental groups was about 6000 mL at 35°C, while that of the total biogas production was close to 7000 mL at 50°C, and the biogas production increased by about 10%. 34 As shown in Figure 3, the total biogas production of the U3 experimental groups was about 6000 mL at 35°C, while that of the total biogas production was close to 7000 mL at 50°C, and the biogas production increased by about 10%.…”
Section: Changes In the Cumulative Biogas Production At Different Tmentioning
confidence: 84%
“…It was found that the biogas production regularity of U3 experimental group was basically the same as that of AD of cow dung alone at 55°C. 34 As shown in Figure 3, the total biogas production of the U3 experimental groups was about 6000 mL at 35°C, while that of the total biogas production was close to 7000 mL at 50°C, and the biogas production increased by about 10%. After calculation, the highest daily biogas production of U3 experimental group at 55°C is 521.4 mL·d −1 , and the unit TS biogas production rate can reach 0.23 L·g −1 .…”
Section: Changes In the Cumulative Biogas Production At Different Tmentioning
confidence: 84%
“…Biogas production from liquid and solid manure does not only contribute to energy supply, but is also an essential measure of integrated manure management strategies to reduce environmental impacts [76,77]. Methane yields depend mainly on animal species [78,79] and further on their type of use, sex, age and diets [80][81][82]. The potential for influencing feedstock characteristics seems small.…”
Section: Unlocking Residuesmentioning
confidence: 99%